Cell-Matrix Interactions Contribute to Barrier Function in Human Colon Organoids - Varani, James; McClintock, Shannon D.; Aslam, Muhammad N. (Frontiers in Medicine, 2022)
The importance of cell-matrix adhesion to barrier control in the colon is unclear. The goals of the present study were to: i) determine if disruption of colon epithelial cell interactions with the extracellular matrix alters permeability control measurement and ii) determine if increasing the elaboration of protein components of cell-matrix adhesion complexes can mitigate the effects of cell-matrix disruption. Human colon organoids were interrogated for transepithelial electrical resistance (TEER) under control conditions and in the presence of Aquamin®, a multi-mineral product. A function-blocking antibody directed at the C-terminal region of the laminin α chain was used in parallel. The effects of Aquamin® on cell-matrix adhesion protein expression were determined in a proteomic screen and by Western blotting. Aquamin® increased the expression of multiple basement membrane, hemidesmosomal and focal adhesion proteins as well as keratin 8 and 18. TEER values were higher in the presence of Aquamin® than they were under control conditions. The blocking antibody reduced TEER values under both conditions but was most effective in the absence of Aquamin®, where expression of cell-matrix adhesion proteins was lower to begin with. These findings provide evidence that cell-matrix interactions contribute to barrier control in the colon.